Hypoxic preconditioning increases survival and pro-angiogenic capacity of human cord blood mesenchymal stromal cells in vitro - Bader, Andreas Matthäus; Bieback, Karen (PLOS ONE, 2015)
Hypoxic preconditioning was shown to improve the therapeutic efficacy of bone marrow-derived multipotent mesenchymal stromal cells (MSCs) upon transplantation in ischemic tissue. Given the interest in clinical applications of umbilical cord blood-derived MSCs, we developed a specific hypoxic preconditioning protocol and investigated its anti-apoptotic and pro-angiogenic effects on cord blood MSCs undergoing simulated ischemia in vitro by subjecting them to hypoxia and nutrient deprivation with or without preceding hypoxic preconditioning. Cell number, metabolic activity, surface marker expression, chromosomal stability, apoptosis (caspases-3/7 activity) and necrosis were determined, and phosphorylation, mRNA expression and protein secretion of selected apoptosis and angiogenesis-regulating factors were quantified. Then, human umbilical vein endothelial cells (HUVEC) were subjected to simulated ischemia in co-culture with hypoxically preconditioned or naïve cord blood MSCs, and HUVEC proliferation was measured. Migration, proliferation and nitric oxide production of HUVECs were determined in presence of cord blood MSC-conditioned medium. Cord blood MSCs proved least sensitive to simulated ischemia when they were preconditioned for 24 h, while their basic behavior, immunophenotype and karyotype in culture remained unchanged. Here, “post-ischemic” cell number and metabolic activity were enhanced and caspase-3/7 activity and lactate dehydrogenase release were reduced as compared to non-preconditioned cells. Phosphorylation of AKT and BAD, mRNA expression of BCL-XL, BAG1 and VEGF, and VEGF protein secretion were higher in preconditioned cells. Hypoxically preconditioned cord blood MSCs enhanced HUVEC proliferation and migration, while nitric oxide production remained unchanged. We conclude that hypoxic preconditioning protects cord blood MSCs by activation of anti-apoptotic signaling mechanisms and enhances their angiogenic potential. Hence, hypoxic preconditioning might be a translationally relevant strategy to increase the tolerance of cord blood MSCs to ischemia and improve their therapeutic efficacy in clinical applications.
Gesehen am 26.02.2018